MRI-detected bone marrow edema in early rheumatoid arthritis. - Taylor, P (2008)
The availability of therapeutics, such as biologics targeting TNF, has enabled marked inhibition of structural damage previously thought to be unavoidable in many patients with rheumatoid arthritis (RA). The importance of physicians being able to reliably identify patients at the greatest risk of disease progression is, therefore, increasing. Many prognostic markers, including MRI-detected pathology at the wrist, have been known for some time to correlate with radiographic RA disease progression on a cohort basis. In a substudy of a clinical trial of two conventional DMARD regimens in a cohort of early RA patients, Hetland et al. explored the relationships between the progression of radiographic erosions and the pathological features identifiable on MRI at baseline, as well as several other putative prognostic markers. Here I discuss the potential implications of this study's findings in understanding the role of bone marrow inflammation in tissue destructive pathways.